Storyplaying: Agency and Narrative in Video Games - Domsch, Sebastian (De Gruyter, 2013)
Incontestably, Future Narratives are most conspicuous in video games: they combine narrative with the major element of all games: agency. The persons who perceive these narratives are not simply readers or spectators but active agents with a range of choices at their disposal that will influence the very narrative they are experiencing: they are players. The narratives thus created are realizations of the multiple possibilities contained in the present of any given gameplay situation. Surveying the latest trends in the field, the volume discusses the complex relationship of narrative and gameplay.